Hands-Free Remote Collaboration Over Video: Exploring Viewer and Streamer Reactions - Unver, Baris; D'Angelo, Sarah; Miller, Matthew; Tang, John; Venolia, Gina; Inkpen, Kori (2018 ACM International Conference on Interactive Surfaces and Spaces, 2018)
Video conferencing is often used to connect geographically distributed users and can be used to help them engage in a shared activity in a mobile setting for remote collaboration. One key limitation of today's systems however is that they typically only provide one camera view, which often requires users to hold a mobile phone during the activity. In this paper, we explore the opportunities and challenges of utilizing multiple cameras to create a hands-free, mobile, remote collaboration experience. Results from a study with 54 participants (18 groups of three) revealed that remote viewers could actively participate in an activity with the help of our system and that both the local participant and remote viewers preferred hands-free mode over traditional video conferencing. Our study also revealed insights on how remote viewers manage multiple camera views and showed how automation can improve the experience.